# differential equations

Show 40 post(s) from this thread on one page
Page 1 of 2 12 Last
• Jul 9th 2007, 08:59 AM
emily28
differential equations
hey all!

ive got two differentail equations which i really cannot do, but my friend suggested using this website so here goes!

a) xy(dy/dx) - 2(y+3)=0

b) (dy/dx) - y=xy5 (i think its a special one but i dont know how to do it!)

sorry about the writing style, i dont know how to use the special maths tool yet but i hope you understand what i mean :P

thank you
• Jul 9th 2007, 09:15 AM
ThePerfectHacker
Quote:

Originally Posted by emily28
a) [I]xy(dy/dx) - 2(y+3)=0

$\displaystyle xyy' = 2(y+3)$
$\displaystyle \frac{yy'}{2(y+3)} = \frac{1}{x}$ (or $\displaystyle y=-3$ is solution).
THis is seperable.
• Jul 9th 2007, 10:27 AM
Krizalid
Quote:

Originally Posted by emily28
hey all!

b) (dy/dx) - y=xy5

\displaystyle \begin{aligned} y' - y &= 5xy\\ y' &= y(5x + 1)\\ \frac{1} {y}~dy &= (5x + 1)~dx \end{aligned}

Now it's easier.
• Jul 9th 2007, 10:33 AM
Krizalid
$\displaystyle y'-y=xy^5\iff\frac{y'}{y^5}-\frac1{y^4}=x$

If this is the equation, then set $\displaystyle u=\frac1{y^4}$
• Jul 9th 2007, 10:52 AM
emily28
oh right, but im still unsure where to go from here becuase its seperable but im still slightly confused:confused:
• Jul 9th 2007, 10:55 AM
Krizalid
But you didn't tell me what's the right equation :D
• Jul 9th 2007, 10:59 AM
emily28
oh right sorry it was

y'-y=xy to the power 5

does this help!!
• Jul 9th 2007, 11:01 AM
Krizalid
Quote:

Originally Posted by Krizalid
$\displaystyle y'-y=xy^5\iff\frac{y'}{y^5}-\frac1{y^4}=x$

If this is the equation, then set $\displaystyle u=\frac1{y^4}$

Follow this, 'cause it's a Bernoulli's differential equation.
• Jul 10th 2007, 11:03 AM
emily28
i understand it upto this point and know its bernolli equation, but i dont know how to solve them at all! could anyone suggest where i should go next :confused:
• Jul 10th 2007, 06:05 PM
topsquark
Quote:

Originally Posted by emily28
oh right sorry it was

y'-y=xy to the power 5

does this help!!

Quote:

Originally Posted by Krizalid
Follow this, 'cause it's a Bernoulli's differential equation.

Quote:

Originally Posted by emily28
i understand it upto this point and know its bernolli equation, but i dont know how to solve them at all! could anyone suggest where i should go next :confused:

Let $\displaystyle u = y^{-4}$ (ie. $\displaystyle y = u^{-1/4}$.)

Then $\displaystyle \frac{du}{dx} = -4 \cdot y^{-5} \frac{dy}{dx}$

Turning this around we get:
$\displaystyle \frac{dy}{dx} = - \frac{1}{4}y^5 \frac{du}{dx} = - \frac{1}{4} u^{-5/4} \frac{du}{dx}$

So the differential equation becomes:
$\displaystyle y'-y=xy^5$

$\displaystyle - \frac{1}{4} u^{-5/4} \frac{du}{dx} - u^{-1/4} = x \cdot u^{-5/4}$<-- Multiply both sides by $\displaystyle u^{5/4}$.

$\displaystyle - \frac{1}{4} \frac{du}{dx} - u = x$

$\displaystyle \frac{du}{dx} + 4 u = -4x$

Now solve this for u(x) and when you get that find y(x).

-Dan
• Jul 10th 2007, 10:39 PM
Jhevon
Quote:

Originally Posted by topsquark

$\displaystyle \frac{du}{dx} + 4 u = -4x$

Now solve this for u(x) and when you get that find y(x).

-Dan

i did the manipulation slightly different from what you did, but we ended up with the same thing. i used the modified equation that Krizalid developed to plug the substitutions into. i think it works out nicer that way, but what do i know, maybe it's just nicer in my weird mind
• Jul 11th 2007, 05:20 AM
emily28
hey, sorry guys im still slightly stumped in how to do the next part...:confused:
• Jul 11th 2007, 05:27 AM
Jhevon
Quote:

Originally Posted by emily28
hey, sorry guys im still slightly stumped in how to do the next part...:confused:

it's a first order differential equation. multiply through by the integrating factor and simplify. (You know how to find integrating factors right? ...do you know what an integrating factor is?)
• Jul 11th 2007, 06:05 AM
topsquark
Quote:

Originally Posted by topsquark
$\displaystyle \frac{du}{dx} + 4 u = -4x$

Quote:

Originally Posted by emily28
hey, sorry guys im still slightly stumped in how to do the next part...:confused:

Solve the homogeneous equation first:
$\displaystyle \frac{du_h}{dx} + 4 u_h = 0$

$\displaystyle \frac{du_h}{dx} = -4 u_h$

What function could $\displaystyle u_h(x)$ be? Since we know that $\displaystyle \frac{d}{dx}e^{bx} = be^{x}$ the function $\displaystyle u_h(x)$ must be an exponential. Thus
$\displaystyle u_h(x) = Ae^{bx}$

Plugging this into the homogeneous equation gives:
$\displaystyle Abe^{bx} = -4Ae^{bx}$

This leaves us with b = -4. So $\displaystyle u_h(x) = Ae^{-4x}$.

Now for the particular solution of $\displaystyle \frac{du}{dx} + 4 u = -4x$. The RHS is a polynomial so we would guess that the particular solution $\displaystyle u_p(x)$ will be a polynomial. So try $\displaystyle u_p(x) = cx + d$. Plugging this into the differential equation gives:
$\displaystyle c + 4 (cx + d) = -4x$

$\displaystyle 4cx + (c + 4d) = -4x$

So we have the simultaneous equations
$\displaystyle 4c = -4$
and
$\displaystyle c + 4d = 0$

Thus c = -1 and d = 1/4. Thus $\displaystyle u_p(x) = -x + \frac{1}{4}$.

Since the differential equation is linear the most general solution to the differential equation will be the sum of the homogenous and particular solutions. Thus
$\displaystyle u(x) = u_h(x) + u_p(x) = Ae^{-4x} - x + \frac{1}{4}$

Now, to get y(x) we know that $\displaystyle y(x) = -\frac{1}{u^{1/4}}$. Thus we finally have that
$\displaystyle y(x) = -\frac{1}{(e^{-4x} - x + \frac{1}{4})^{1/4}} = -\frac{1}{\sqrt[4]{e^{-4x} - x + \frac{1}{4}}}$

-Dan
• Jul 11th 2007, 06:59 AM
emily28
i dont that i was meant to look at particular solutions and expenituals, is there another way to do it using perhaps a different method, as i havent covered this in class and dont think the teacher would want me to approach it this way?:confused:
Show 40 post(s) from this thread on one page
Page 1 of 2 12 Last